CHAINS OF COMMAND - 367802 Brown, Dale ,1956- eauthor (London, :)
Two years after Operation Desert Storm, the problems facing military forces around the world have changed dramatically. In the US, active-duty military units have been drastically cut and reserve forces built up. Then an unusual mission comes up. By the author of "Night of the Hawk".